Original educational computer program "Trauma" and its application in education of paramedic students — preliminary results - Trzepizur, Magdalena; Statowski, Wojciech; Myrcik, Dariusz; Makarska, Joanna; Syrkiewicz-Świtała, Magdalena (Journal of Medical Science, 2019)
Education through simulation is becoming increasingly popular in medical academic environment. This is the best teaching method enabling the creation of real situations in risk-free conditions. Decision-making games can be successfully used in the educational process of future medical staff. The aim of the work was to create a didactic computer program "Trauma", analyze its impact on students' knowledge on the direction of medical rescue and evaluate the attractiveness of classes conducted with the use of this method. The results show that the use of the "Trauma" program in didactics has allowed for the improvement of the level of knowledge and skills of students taking part in the study in the field of trauma patients’ treatment. In the assessment of students, the classes during which the program was used were interesting. The vast majority of respondents would like to participate in such classes again.